Petits récits: creative perspectives of Chinese encounters in Zambia - Mwaba, Stary (Rhodes University, Faculty of Humanities, Department of Fine Art, 2020)
This mini-thesis, which supports my MFA exhibition Black Mountain, articulates on-the- ground creative perspectives of the Zambia-China discourse, through the representation of little narratives - les petits récits - connected to personal experiences. Through my creative production as an artist, I respond to perceptions of the Chinese presence in Africa. I utilize historical and contemporary personal narratives to complicate existing perceptions of Chinese presence in my home context of Zambia. "Petit récits" , or "little narratives" , in Francois Lyotard's term, refers to personal stories of individuals that subvert dominant master-narratives and their legitimization in social-cultural structure. In the case of China's presence in Zambia, I refer to the dichotomized narratives in the media as metanarratives which pay little attention to the people on the ground and propose the approach of "little narratives" to foreground the lived experiences of Zambians who have individual encounters with Chinese in various social spaces. By employing the narratives of my family members through installations, paintings, and drawings, I intervene in a broader China-Africa discourse that is often driven by economics and politics, and I attach importance to the little narratives. In my thesis I divide my material into three chapters; each chapter grows out of an encounter with the presence of China (and Chinese people) in Zambia in relation to the very personal narratives of family members - Zoë my daughter, my grandma, and Ngolo my cousin. The first chapter focuses on my work Chinese Cabbage as my entry point to this topic, which is based on a school experiment I did with my daughter Zoë. In this chapter I also discuss the current discourses around China's presence. Chapter two revisits the Zambian-Chinese historical encounters in memory of my grandma's insaka stories about the construction of TAZARA Railway, and thus my works discussed in this chapter attach importance to the individual engagements from a historical perspective. Chapter three discusses in particular the controversial issues around Black Mountain and the works inspired by my cousin Ngolo's stories of mining in Black Mountain and dealing with the Chinese traders.
Keywords: Personal narratives; Lyotard, Jean-FrancÌ§ois, 1924-1998; Art and society -- Zambia; Social practice (Art) -- Zambia; Art and globalization -- Zambia; China -- Relations -- Zambia; Storytelling in art; Colonization in art